2020
DOI: 10.1111/gcb.15043
|View full text |Cite
|
Sign up to set email alerts
|

Plastic pollution in croplands threatens long‐term food security

Abstract: Plastic pollution is a global concern given its prevalence in aquatic and terrestrial ecosystems. Studies have been conducted on the distribution and impact of plastic pollution in marine ecosystems, but little is known on terrestrial ecosystems. Plastic mulch has been widely used to increase crop yields worldwide, yet the impact of plastic residues in cropland soils to soil health and crop production in the long term remained unclear. In this paper, using a global meta-analysis, we found that the use of plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 230 publications
(89 citation statements)
references
References 26 publications
1
88
0
Order By: Relevance
“…Plastics (particularly MPs) in the agricultural soil [201,202], vegetables and fruits [203], and seafood [204,205] are a potential threat to sustainable food production system and food security. Zhang et al [206] reported that the accumulation of plastic film residues in the field negatively impacts the physicochemical properties linked to soil health and negatively impacts food production. They showed that crop yield decreased at the mean rate of 3% for an additional 100 kg/ha of film residue and there were also negative impacts on plant height, root growth, and soil properties such as soil water infiltration rates, soil organic matter, and soil available phosphorus.…”
Section: Sdg 2 (End Hunger Achieve Food Security and Improved Nutrition And Promote Sustainable Agriculture)mentioning
confidence: 99%
“…Plastics (particularly MPs) in the agricultural soil [201,202], vegetables and fruits [203], and seafood [204,205] are a potential threat to sustainable food production system and food security. Zhang et al [206] reported that the accumulation of plastic film residues in the field negatively impacts the physicochemical properties linked to soil health and negatively impacts food production. They showed that crop yield decreased at the mean rate of 3% for an additional 100 kg/ha of film residue and there were also negative impacts on plant height, root growth, and soil properties such as soil water infiltration rates, soil organic matter, and soil available phosphorus.…”
Section: Sdg 2 (End Hunger Achieve Food Security and Improved Nutrition And Promote Sustainable Agriculture)mentioning
confidence: 99%
“…Similar issues can be found in microplastics in soil that are derived from the misuse of plastic film mulch and other plastic products. To increase crop yields, plastic mulch is widely used, mainly in dryland regions to maintain soil moisture and in cold regions to increase soil temperature [ 12 ]. However, the low recovery of plastic mulch results in the accumulation of a large amount of plastic film residues in soils that alter their physicochemical properties, threatening plant growth in the long term.…”
Section: Pollutantsmentioning
confidence: 99%
“…However, the low recovery of plastic mulch results in the accumulation of a large amount of plastic film residues in soils that alter their physicochemical properties, threatening plant growth in the long term. Meanwhile, these small pieces of plastic and their additives such as phthalates in soil can be taken up by plants and transferred along the food chain to consumers, including humans [ 12 ]. These microplastics have been detected in the excreta of humans in many countries.…”
Section: Pollutantsmentioning
confidence: 99%
“…Nevertheless 'phthalates' have also been labeled as toxic and possible endocrine disruptors (Sathyanarayana, 2008;Sax, 2010). More recently, microplastics and bigger fragments of plastic are recognized as specific problem found worldwide in oceans and terrestrial environments (Gao et al, 2019;Zhang et al, 2020). Microplastics were recently found in the snow of once pristine Mount Everest (Napper et al, 2020), high mountain lakes of Alps (Pastorino et al, 2020), as well as in the deep-marine environments (Kane & Clare, 2019).…”
Section: Introductionmentioning
confidence: 99%